Reassessing the “Asia Minor Catastrophe” of 1922: - Dimitris Kamouzis (Diasporas: Circulations, Migrations, Histoire)
The year 1922 undoubtedly constitutes the most painful collective trauma in the history of modern Greece. It signifies the “Asia Minor Catastrophe”, a term used to describe the defeat of the Greek army in the Greco-Turkish war of 1919‑1922 and the subsequent violent uprooting from the Turkish coastline and inner Asia Minor of approximately 1,300,000 Orthodox Greeks, who ultimately settled in Greece. This paper focuses on the various processes of collective memory formation and on the gradual development of a unique refugee identity in relation to the host country and its people during the first years of the Asia Minor Greeks’ settlement in Greece.